Macroeconomic experiences and risk taking of euro area households - Miguel Ampudia; Michael Ehrmann (European Central Bank (ECB), 2014)
This paper studies to what extent the experiences of households shape their willingness to take financial risks. It follows the methodology of Malmendier and Nagel (2011) and applies it to a novel data set on household finances covering euro area households. We show that experienced stock market returns matter in a statistically significant and economically substantial fashion: better experiences increase the financial risk households are willing to take as well as stock market participation along the intensive and the extensive margin. We find that more distant experiences receive a somewhat lower (but still substantial) weight than the corresponding findings suggest for the United States. Furthermore, there are additional effects stemming from the experience of extreme stock market downturns. Households in countries that witnessed a particularly severe 2008 stock market crash give substantially more weight to the most recent experience, suggesting that in these countries an even more pronounced underinvestment in the stock market should be expected in the years to come. The evidence highlights the relevance of personal experiences for household behaviour.
Keywords: D03; D14; D83; G11; 330; household finance; learning; portfolio choice; rare disasters; risk-taking behavior